Market power and fiscal policy in OECD countries - Afonso, António (2010)
We compute average mark-ups as a measure of market power throughout time and study their interaction with fiscal policy and macroeconomic variables in a VAR framework. From impulse-response functions the results, with annual data for a set of 14 OECD countries covering the period 1970-2007, show that the mark-up (i) depicts a pro-cyclical behaviour with productivity shocks and (ii) a mildly counter-cyclical behaviour with fiscal spending shocks. We also use a Panel Vector Auto-Regression analysis, increasing the efficiency in the estimations, which confirms the country-specific results.